A case of glandular odontogenic cyst of the maxilla - SEGAWA, Kiyoshi; KASAHARA, Shintaro; TAKEDA, Yasunori; IZUMISAWA, Mitsuru; KUDO, Keigo (Japanese Journal of Oral and Maxillofacial Surgery, 2001)
Glandular odontogenic cyst is a rare jaw bone cyst of odontogenic origin, first described in 1988 by Gardner et al. Radiologically, a well-defined unilocular cyst lesion is seen. Histologic features include a thin layer of epithelium with surface cilia and glandular or pseudoglandular structures. A case of glandular odontogenic cyst of the maxilla is reported.